Postpartum Ovarian Vein Thrombosis: Two Cases and Review of Literature - Amos A. Akinbiyi; Rita Nguyen; Michael Katz (Case Reports in Medicine)
Introduction. We presented two cases of late presentation of ovarian vein thrombosis postpartum following vaginal delivery and cesarean section within a short period in our institution. Both of them had pelvic pain following their deliveries which was associated with fever and chills. One of them was quite a big-sized thrombophlebitic vein which was about 10×6×5 centimeters following a computed tomography. They were both treated initially for urinary tract infection, while a large ovarian vein thrombosis was not diagnosed in the second patient until her emergency department admission. Conclusion. Ovarian vein thrombosis is rare, but could present late, and difficult to diagnose, hence, should be considered as a differential diagnosis in a postpartum woman with fever and tender pelvic mass.